Trei tabuuri ale societății primitive - Maior, Claudia (Theatrical Research, 2024)
Three Taboos of Primitive Societies The study analyses three of the most powerful taboos of primitive society: the taboo of living corpses, the taboo of masters and that of incest. Starting out from Freud’s assumption according to which any ritual practice has its origin in primordial crime, we can assert that all taboos of primitive societies are derived from the taboo of death. It is from this taboo that all others are derived, becoming consequences of the fear of death: the dream, the trance, crime, visions, violence. This obsession with death gives birth to monsters. Among its offspring we might count: incest, animism, the act of relating to enemies, the tendency to associate with a master, the fear of living corpses.